Immigrants’ Cross‐Border Interaction and the Pandemic: Estonians Living in Finland - Jauhiainen, Jussi S. (Cogitatio Press, 2026)
Although major Covid‐19 restrictions have ended, their impact on how immigrant communities navigate physical and digital mobility continues to demand attention. This article examines shifts in cross‐border offline and online interactions before and after the pandemic’s most disruptive phase, focusing on Estonians in Finland, the country’s second‐largest immigrant group. Survey data from 2,398 respondents shows how the pandemic reconfigured cross‐border activity spaces: Physical travel to Estonia sharply declined while digital contact via phone and social media intensified. The pandemic altered immigrants’ spatial agency and expanded digital spaces of interaction. Digital communication and interaction did not replace embodied mobility nor generate hybrid transnational identities; instead, it reinforced emotional and cultural attachments to Estonia. After restrictions eased, in‐person visits not only resumed but exceeded pre‐pandemic levels. This case highlights how digital tools reconfigure cross‐border activity spaces and belonging in highly specific ways, shaped by ethnic, spatial, and socio‐technical factors. Ensuring equitable digital inclusion policies remains essential for sustaining immigrants’ well‐being and spatial agency.